Permainan Moncer untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Kelas VI Sekolah Dasar - Nuryati, Tutuk (Jurnal Didaktika Pendidikan Dasar, 2023)
The learning outcomes of class VI students at SDN Bancamara III regarding Natural Appearance and Social Conditions of Neighboring Countries still do not meet the KKM set by the school. Of the 21 students, only 2 students could meet the KKM while the others could not meet the KKM, the cause was the lack of motivation of students in participating in learning. Students feel bored when studying indoors. Students have difficulty understanding social studies material because the majority of it is material that needs to be memorized. This research uses the PTK method which consists of two cycles. Each cycle consists of four steps, namely planning, implementation, observation and reflection. The aim of this research is to describe the use of the MONCER (Smart Monopoly) game media on Natural and Social Appearance material from neighboring countries for class VI students at SDN Bancamara III, Dungkek District, Sumenep Regency. From the results of data analysis, it was found that student learning outcomes increased from an average of 38.09% classical completeness in cycle I to 90.47% in cycle II. Based on the data obtained, it can be concluded that the use of MONCER game media can improve student learning outcomes.